METAFORA KONSEPTUAL DALAM NOVEL TERJEMAHAN “PEREMPUAN DI TITIK NOL” OLEH AMIR SUTAARGA: TINJAUAN STILISTIKA - Yuliza Susanti, Devi; Darwis, Muhammad; Tamasse, Tamasse (Universitas Hasanuddin, 2023)
This research aims to describe the source of the metaphors found in the translated novel Perempuan di Titik Nol and the correspondence between the source domain and the target domain in the novel Perempuan di Titik Nol. The data in this research are in the form of words, sentences, and expressions that are indicated as metaphors in the translated novel Perempuan di Titik Nol by Amir Sutaarga. The results of this research reveal that six types of source domains have been identified, four types of transmission that appear in the translated novel Perempuan di Titik Nol. The metaphors in this novel play a role in bringing concepts that are difficult to understand into the real world through the use of concrete objects so that readers can better connect with the meaning the translator wants to convey.